Increased CD8+ T cell response to Epstein-Barr virus lytic antigens in the active phase of multiple sclerosis. - Daniela F Angelini; Barbara Serafini; Eleonora Piras; Martina Severa; Eliana M Coccia; Barbara Rosicarelli; Serena Ruggieri; Claudio Gasperini; Fabio Buttari; Diego Centonze; Rosella Mechelli; Marco Salvetti; et al. (PLoS Pathogens)
It has long been known that multiple sclerosis (MS) is associated with an increased Epstein-Barr virus (EBV) seroprevalence and high immune reactivity to EBV and that infectious mononucleosis increases MS risk. This evidence led to postulate that EBV infection plays a role in MS etiopathogenesis, although the mechanisms are debated. This study was designed to assess the prevalence and magnitude of CD8+ T-cell responses to EBV latent (EBNA-3A, LMP-2A) and lytic (BZLF-1, BMLF-1) antigens in relapsing-remitting MS patients (n = 113) and healthy donors (HD) (n = 43) and to investigate whether the EBV-specific CD8+ T cell response correlates with disease activity, as defined by clinical evaluation and gadolinium-enhanced magnetic resonance imaging. Using HLA class I pentamers, lytic antigen-specific CD8+ T cell responses were detected in fewer untreated inactive MS patients than in active MS patients and HD while the frequency of CD8+ T cells specific for EBV lytic and latent antigens was higher in active and inactive MS patients, respectively. In contrast, the CD8+ T cell response to cytomegalovirus did not differ between HD and MS patients, irrespective of the disease phase. Marked differences in the prevalence of EBV-specific CD8+ T cell responses were observed in patients treated with interferon-β and natalizumab, two licensed drugs for relapsing-remitting MS. Longitudinal studies revealed expansion of CD8+ T cells specific for EBV lytic antigens during active disease in untreated MS patients but not in relapse-free, natalizumab-treated patients. Analysis of post-mortem MS brain samples showed expression of the EBV lytic protein BZLF-1 and interactions between cytotoxic CD8+ T cells and EBV lytically infected plasma cells in inflammatory white matter lesions and meninges. We therefore propose that inability to control EBV infection during inactive MS could set the stage for intracerebral viral reactivation and disease relapse.